Motor Cortex Plasticity Predicts Recovery in Acute Stroke - Vincenzo Di Lazzaro; Paolo Profice; Fabio Pilato; Fioravante Capone; Federico Ranieri; Patrizio Pasqualetti; Cesare Colosimo; Emanuele Pravatà; Alessandro Cianfoni; M. Dileone (2009)
Repetitive transcranial magnetic stimulation of the brain given as intermittent theta burst stimulation (iTBS) can induce long-term potentiation (LTP)–like changes in the stimulated hemisphere and long-term depression (LTD)–like changes in the opposite hemisphere. We evaluated whether LTP- and LTD-like changes produced by iTBS in acute stroke correlate with outcome at 6 months. We evaluated the excitability of affected hemisphere (AH) and unaffected hemisphere (UH) by measuring motor threshold and motor-evoked potential (MEP) amplitude under baseline conditions and after iTBS of AH in 17 patients with acute ischemic stroke. Baseline amplitude of MEPs elicited from AH was significantly smaller than that of MEPs elicited from UH, and baseline motor threshold was higher for the AH. Higher baseline MEP values in UH correlated with poor prognosis. iTBS produced a significant increase in MEP amplitude for AH that was significantly correlated with recovery. A nonsignificant decrease in MEP amplitude was observed for the UH. When the decrease in the amplitude of UH MEPs was added to the regression model, the correlation was even higher. Functional recovery is directly correlated with LTP-like changes in AH and LTD-like changes in UH and inversely correlated with the baseline excitability of UH.